An at-scale tailless flapping wing hummingbird robot: II. Flight control in hovering and trajectory tracking. (1st March 2023) - Fei, Fan; Tu, Zhan; Deng, Xinyan
Abstract: Flight control such as stable hovering and trajectory tracking of tailless flapping-wing micro aerial vehicles is a challenging task. Given the constraint on actuation capability, flight control authority is limited beyond sufficient lift generation. In addition, the highly nonlinear and inherently unstable vehicle dynamics, unsteady aerodynamics, wing motion caused body oscillations, and mechanism asymmetries and imperfections due to fabrication process, all pose challenges to flight control. In this work, we propose a systematic onboard control method to address such challenges. In particular, with a systematic comparative study, a nonlinear flight controller incorporating parameter adaptation and robust control demonstrates the preferred performances. Such a controller is designed to address time-varying system uncertainty in flapping flight. The proposed controller is validated on a 12-g at-scale tailless hummingbird robot equipped with two actuators. Maneuver experiments have been successfully performed by the proposed hummingbird robot, including stable hovering, waypoint and trajectory tracking, and stabilization under severe wing asymmetries.